2007
DOI: 10.21273/jashs.132.5.603
|View full text |Cite
|
Sign up to set email alerts
|

Gas Exchange, Water Status, and Growth of Pepper Seedlings Exposed to Transient Water Deficit Stress are Differentially Altered by Antitranspirants

Abstract: Successful field establishment of vegetable transplants often depends on the ability of young seedlings to tolerate various biotic and abiotic stresses after transplanting. Treatments that limit transpirational water loss could improve plant survival and stand establishment. In this study we evaluated growth and physiological responses of pepper (Capsicum annuum L.) seedlings to foliar application of chemical plant regulators [abscisic acid (ABA) and aminoethoxyvinylglycine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…However, 8 d of drought was excessive and photosynthesis was negligible. Goreta et al (2007) found that AT did not significantly influence leaf gas exchange or water relations of pepper seedlings exposed to water deficit. However, in agreement with our results, Plaut et al (2004) found that acrylic film application decreased gs and A CO 2 of greenhouse-grown pepper plants.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, 8 d of drought was excessive and photosynthesis was negligible. Goreta et al (2007) found that AT did not significantly influence leaf gas exchange or water relations of pepper seedlings exposed to water deficit. However, in agreement with our results, Plaut et al (2004) found that acrylic film application decreased gs and A CO 2 of greenhouse-grown pepper plants.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to the effect of [CO 2 ] on stomatal behavior, foliar application of antitranspirants is a promising tool for regulating transpiration to maintain a favorable plant water status (Goreta et al, 2007). The formation of thin films can also minimize the escape of water from the plant by decreasing stomatal conductance, thus reducing transpirational losses, improving plant water status and reducing wilting and leaf abscission (Gu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This mode of action proposes a new stress-management approach to reducing transplant shock. Most stress-management techniques reported in previous studies aim to reduce postplanting water stress by limiting transpiration (Berkowitz and Rabin, 1988;del Amor et al, 2010;Goreta et al, 2007;Iriti et al, 2009;Moftah and Al-Humaid, 2005) or by activating defense mechanisms in molecular processes (Tuteja and Sarvajeet, 2012). The main drawback of these techniques is that their beneficial stress control effects are limited under optimum field conditions (Agehara and Leskovar, 2012;Berkowitz and Rabin, 1988;Moftah and Al-Humaid, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Other negative side effects of abscisic acid include leaf chlorosis, leaf abscission, and excessive inhibition in leaf expansion and stem elongation (Agehara and Leskovar, 2014aLeskovar, , 2014bLeskovar, , 2015Leskovar, , 2017Park et al, 2016). In addition, the performance of film-forming antitranspirants is limited primarily on the adaxial leaf surface and is dependent highly on spray coverage (Goreta et al, 2007). By contrast, preplant 1-MCP treatment can improve postplanting performance of vegetable seedlings even when postplanting stress is minimal in the field, and it has no negative side effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation